2021
DOI: 10.1002/pits.22581
|View full text |Cite
|
Sign up to set email alerts
|

Applying the demand–control–support model on burnout in students: A meta‐analysis

Abstract: Fourteen empirical studies on academic burnout were synthesized and reviewed with a meta‐analytic approach based on the framework of job demand, control, support model. It was found that demand, control, and support were associated with academic burnout. The three dimensions of burnout were negatively related to demand and positively related to control and support. In terms of types of demand, which were classified into psychological and physical demands, moderating effects were observed on the three burnout d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 103 publications
0
9
0
6
Order By: Relevance
“…Lastly, putting these results in perspective, we can consider the few statistically significant effects (positive relationship with community support and negative relationship with colleagues' support) as suggestive rather than solid evidence. In the study by Kim et al [100], fourteen empirical studies on burnout in students were reviewed and support was found to be negatively associated with all three burnout dimensions. Similarly, a systematic review of the work environment and burnout, not confined to any specific occupational group, showed moderately strong evidence of a relationship between low workplace support and increased emotional exhaustion [101].…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
“…Lastly, putting these results in perspective, we can consider the few statistically significant effects (positive relationship with community support and negative relationship with colleagues' support) as suggestive rather than solid evidence. In the study by Kim et al [100], fourteen empirical studies on burnout in students were reviewed and support was found to be negatively associated with all three burnout dimensions. Similarly, a systematic review of the work environment and burnout, not confined to any specific occupational group, showed moderately strong evidence of a relationship between low workplace support and increased emotional exhaustion [101].…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
“…Lee and Ashforth ( 73 ) believed that compared with cynicism and inefficacy in job burnout, emotional exhaustion has a higher correlation with demands (including time pressure as an indicator) and resource variables. More recently, Kim et al ( 33 ) found a positive correlation between study demands and emotional exhaustion in the school setting through a meta-analysis. Similar findings show a significant positive correlation between study demands and emotional exhaustion among high school students ( 34 ) and college students ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…As one of the study resources, perceived social support has been widely discussed in a variety of studies ( 20 , 26 28 ). Many studies show that social support is negatively correlated with student burnout ( 27 , 33 , 48 ). Social support from school or teachers, parents, and peers is negatively correlated with student burnout ( 27 , 45 47 ); that is probably because social support has a promotive effect on reducing student emotional exhaustion ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Academic burnout has three main manifestations, namely exhaustion due to the demands of learning (emotional exhaustion), a cynical or transcendental attitude toward one’s own learning (depersonalization), and a sense of incompetence and difficulty in generating satisfaction as a student [ 42 ] as well as a negative evaluation of the educational environment (low personal achievement) [ 43 ]. The main characteristic of burnout is a combination of exhaustion (low activation) and cynicism (low identity), while the opposite of academic dedication is characterized by vitality (high activation) and dedication (high identity) [ 44 ].…”
Section: Literature Reviewmentioning
confidence: 99%